Familial mediterranean fever: a fascinating model of inherited autoinflammatory disorder. (14th October 2013) - Portincasa, Piero; Scaccianoce, Giuseppe; Palasciano, Giuseppe
Abstract Background Familial Mediterranean fever (FMF) is a rare inherited autosomal recessive autoinflammatory disorder characterized by recurrent and self‐limited episodes of fever and painful serositis, lasting 1–3 days. FMF occurs almost exclusively among ethnic groups of the Mediterranean basin, although cases have also been found in Japan and Korean populations. Diagnosis is based on clinical features, response to colchicine and genetic analysis. Novel drugs are emerging, allowing better management of colchicine‐resistant/colchicine‐intolerant patients. This review aims to attract the attention of the readers on differential diagnosis and management of patients with FMF. Methods The current state‐of‐the‐art on FMF is outlined, with respect to epidemiological, genetic, pathophysiological and therapeutic characteristics, based on critical analysis of solid scientific literature. Results FMF is more frequent than it was thought before. The phenotypic expression of M694V is more severe than that of V726A. Patients with M694V/M694V homozygosity are exposed to a higher risk of developing renal amyloidosis, arthritis, dermatologic and oral lesions, higher fever and more frequent painful attacks. Life‐long therapy with colchicine (1·0–2·4 mg/day) is effective and safe to prevent recurrent attacks and renal amyloidosis and to reverse proteinuria. In nonresponder patients, alternative novel approaches include interleukin‐1 receptor antagonist anakinra and the interleukin‐1 decoy receptor rilonacept. Conclusions The prognosis of FMF is normal if AA amyloidosis is prevented. Colchicine remains the first‐line therapy to treat pain and prevent amyloidosis. A follow‐up should include clinical evaluation, therapeutic adjustments, measurement of serum amyloid A and proteinuria.